Piano Sonatas & String Quartets 1 - Rădulescu, Horațiu 1942-2008; Clarke, Stephen; Gilmore, Bob 1961-2015; JACK Quartet (USA) (New York Mode, 2016)
The first volume in a projected series combining Radulescus complete Piano Sonatas and String Quartets there are six of each on Mode performed by the superb JACK Quartet and Stephen Clarke (piano).In the 1970s, Horatiu Radulescu began exploring and composing begun composing what he called plasmatic music, in which sound was conceived as an endless ocean of vibrations, as opposed to the traditional way in which music treats sound as a fabric of discrete scale steps. His music is linked to the spectral music school. Radulescus Fifth String Quartet is one of the key works in his output. It is in some ways the richest manifestation of the body of string techniques he had developed for his music. It consists of 29 sections/pages which richly evocative titles, each lasting about 1 minute.The Second Piano Sonata is inspired by the Tao of Chinese philosopher Lao tzu (6-5 BC). The first movement, Immanence, opens with a powerful sonority built from spectral functions which gives a sense of immensity and strength. The Fifth Piano Sonata makes abundant use more so than any of the other sonatas of Romanian folk material, which is absorbed and integrated into Radulescus spectral language.
String Quartet No.5 before the universe was born, op. 89 (1990-95) -- Piano Sonata No.5 settle your dust, this is the primal identity, op. 106 (2003): 1. The path into the light seems dark; 2. Darkness within darkness. / The gateway to all understanding; 3. Use your own light / and return to the source of light. / This is called practicing eternity 4:31 -- Piano Sonata No.2 being and non-being create each other, op. 82 (1991): 1. Immanence; 2. Byzantine Bells; 3. Joy
Keywords: 20th Century (1901-2000); String quartet; Sonata; Piano; Taoism; Spectral music; Romania